GAMBARAN INFEKSI PARASIT USUS PADA SPESIMEN FESES PASIEN DIARE YANG DIRAWAT DI BANGSAL ANAK RSUP DR. M. DJAMIL PADANG TAHUN 2016-2021 - Daryatri, Aviranti Salsabila; Nurhayati, Nurhayati; Hamdani, Rita; Rusjdi, Selfi Renita; Meinapuri, Malinda; Irawati, Lili (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Diarrhea is a change of the feces form as well as an increase of the frequency of defecation more than three times in 24 hours. Causes of diarrhea can be either infection or non-infection. The cause of infectious diarrhea that is often unnoticed is intestinal parasite infection. Epidemiologically, there is not much data about intestinal parasite infection in diarrhea patients. The aim of this study is to describe the description of intestinal parasite infection in feces specimen of diarrhea patients that treated at the pediatric ward of Dr. M. Djamil Padang Hospital in 2016-2021 .This research is a descriptive observational research using secondary data from the medical records of diarrhea patients that treated at the pediatric ward. The sample includes all that fulfilled the criteria, with total 108 patients. The data were analyzed using univariate analysis. The results showed that the majority of patients were in the age between 0 to 5 years old (56,5%) and male (33.8%). Most diarrhea was acute diarrhea (97,2%) with mild to moderate dehydration (76,9%). Patients that infected by intestinal parasite were found in three people (2.8%) with the same parasite which was Entamoeba histolytica in the cyst stage, and also there were no helminth found in this research. Laboratory examination showed that all three had normal Hb and leukocyte levels, there was no blood in the feces and one had mucus in the feces. Three diarrhea patients that infected by intestinal parasite were given rehydration therapy (100%) and antiparasitic drug such as metronidazole (100%). The conclusion of this study is all of the feces specimens of diarrhea patients from this research described that the diarrhea was not caused by intestinal parasites.